2016
DOI: 10.1097/sla.0000000000001305
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Surgical Outcome 1 Year After Open and Laparoscopic Incisional Hernia Repair

Abstract: Patients with incisional hernia benefit substantially from surgery concerning QoL, independent of surgical technique. An event-free recovery occurred frequently after laparoscopic surgery. SF-36 seems well suited for assessing surgical outcome in patients after incisional hernia repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 25 publications
0
38
2
Order By: Relevance
“…All studies used a minimum mesh overlap of 3–5 cm. Thirty studies reported the percentage of patients at last follow‐up, with a median of 98 (range 76–100) per cent. Follow‐up was given as either a mean or median value, with an overall median of 22 (range 6–64) months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies used a minimum mesh overlap of 3–5 cm. Thirty studies reported the percentage of patients at last follow‐up, with a median of 98 (range 76–100) per cent. Follow‐up was given as either a mean or median value, with an overall median of 22 (range 6–64) months.…”
Section: Resultsmentioning
confidence: 99%
“…There was an unclear risk of attrition bias in three studies as they did not describe patients lost to follow‐up. The risk of funding bias was unclear in two studies that did not describe the source of funding, and high in five studies that were funded by industry. The remaining three studies reported no funding from industry and had a low risk of funding bias.…”
Section: Resultsmentioning
confidence: 99%
“…A generic validated QOL scale should be more acceptable to population and observers and should be consistent and acceptable in both short and long term follow up. [18][19][20][21][22][23][24][25][26][27][28][29][30][31] Literature review has showed that, it is best to use a generic scale with a disease specific scale along with a validated pain scale that can cover the immediate postoperative period. 8,13,14 Pain scores should be used in the peri-operative period to determine if patient has developed any acute pain or his pre-operative pain is continuing and becoming a chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Time frame for follow up is the most diverged subject in the literature, where quality of life was measured as soon as next day of surgery to up to five years. [18][19][20][21][22][23][24][25][26][27][28][29][30][31] No consistency was found in the follow up period and in different studies it ranges from days to years. Literature review also did not help to conclude the best time for follow up.…”
Section: Discussionmentioning
confidence: 99%
“…One obvious goal in ventral hernia repair is to improve patients' QoL. Only a few studies have measured the influence of LIVHR on QoL [22][23][24]. According to these outcomes, LIVHR appears to reduce chronic pain and physical impairment and improves long-term QoL.…”
mentioning
confidence: 99%